CHARACTERIZATION AND EVALUATION OF APPEARANCE RICE (Oryza sativa L.) LOCAL EAST TIMOR AND RICE INDONESIA - Baptista, Abilio Tilman; Damanhuri; Barunawati, Nunun (International Journal of Research -GRANTHAALAYAH, 2018)
Rice is an important commodity for the majority of the population, especially in the continent of Asia use rice as a staple food. The state of Indonesia and East Timor, rice as the main food source that needs continue to increase because in addition to the population continues to grow at a rate of increase of about 2% per year, as well as the change in consumption pattern of the population of non-rice to the rice. Interest characterization and evaluation of the appearance of rice(Oryza Sativa L.) locally Timor Leste and Indonesian rice are getting Local rice genotypes Timorese suitable for cultivated in paddy fields. This research using a randomized block design (RBD) consisted of 9 treatments and 3 replications. The materials used are high-yielding rice varieties namely IR-3 64, Ciherang, Cimelati and 6 local rice genotypes Timor Leste, namely Hare Foam, Fafulu Hare, Hare Bauk Morin, Mean Hare, Hare and Hare Modok Fulan. Results showed that the highest plant length at the age of 10 MST contained in the local rice Hare Bauk Morin(134.67 cm), Number of tillers(40.30) the number of leaves(4.64).Flowering date and time of harvest shortest genotypes present in Morin namely Hare Bauk flowering date (39 days) and time of harvest (105 days). The highest number of panicles contained in Hare Mean genotype, high-yielding varieties IR64, Ciherang and Cimelati. The length of the longest panicle genotypes present in Foam Hare, Hare Hare Fafulu, and Fulan. The number of filled grains per panicle most contained in superior varieties IR64, Ciherang and Cimelati. The highest weight of 1000 grains contained in Cimelati varieties (vu3) with Hare Bauk Morin, IR64 and Cherang varieties. The highest rice yield for local rice genotypes present in Hare Bauk Morin (G3) of 9.79 ton.Ha-1 while yielding varieties there exist varieties Cherang (vu2) of 9.74 ton.Ha-1.